Dr H. R. Mill's Antarctic Library - Wordie, J. M. (Polar Record, 1946)
Dr Mill's well-known collection of Antarctic books is without doubt the most extensive and interesting collection of Antarctic books in Britain. The most important volumes reached Cambridge in 1939, but on account of the war the main part of the library remained at Dr Mill's home at Dormans Park. These have now arrived at the Institute and the collection has been placed on the shelves.